A novel doublet extreme learning machines for Delta 3D printer fault diagnosis using attitude sensor. (March 2021) - Guo, Jianwen; Li, Xiaoyan; Liu, Zhiyuan; Zhang, Shaohui; Wu, Jiapeng; Li, Chuan; Long, Jianyu
Abstract: Extreme learning machine (ELM) has better operation efficiency in fault diagnosis. However, the recognition accuracy of ELM algorithm is actually affected by the activation function. Moreover, most of the testing dataset are coming from high precision and expensive sensors. In this paper, raw data are collected by a low-cost attitude sensor, which is installed on the mobile platform of a delta 3D printer. A doublet activation function is proposed to improve the performance of ELM, named doublet ELM (DELM). The proposed method is evaluated using experimental data collected from the 3D printer, and its advantages are demonstrated by comparing with other activation functions. The experimental results indicate that the proposed method leads to the highest accuracy in different hidden nodes and the testing classification rate achieves 93% and 96% using only 8.33% of the dataset for model training, for R75 and R90 sub-datasets, respectively. Moreover, compared with peer methods, such as random forest, echo state network, and so on, the results show that the present DELM exhibits the best performance in small-sample and improves the accuracy of the 3D printer fault diagnosis. Highlights: An attitude sensor was mounted on the moving platform to monitor printer conditions. A doublet ELM activation function is proposed based on the attitude data. The proposed method yields the highest classification rates in the small-sample case.